Environmental impacts of a highly congested section of the Pan-American highway in Peru using life cycle assessment - Veran-Leigh, D (2019)
Financial support was given by the Peruvian Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica (CONCYTEC).